A Comparative Analysis of Literate Language Features of Chinese ESL Learners' Narrative versus Expository Writing. (26th September 2020) - Jiang, Xiangyu; Chen, Liang; Zhou, Qin
Abstract : This study evaluated the narrative and expository English writing corpus from 20 Chinese English learners at three linguistic levels: the use of literate words (elaborated noun phrases, conjunctions, adverbs, and mental state verbs), the degree of sentence complexity, and the use of subordinate clauses (nominal, adverbial and relative clauses). Results first showed a genre effect on literate word use but not on utterance length and clausal density. Specifically, there were more elaborated noun phrases and conjunctions in expository texts, but more adverbs in narrative texts. Results also revealed a genre effect on the use of relative clauses but not on other clauses. Finally, a strong correlation between literate word use and the production of complex syntax was found after controlling for the effects of genre. These results highlight the need for genre-dependent writing instruction to make students aware of the different language resources expected across genres as specific contexts of communication.